2014
DOI: 10.1002/rcm.7079
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and limitations of reaction cell and sector field inductively coupled plasma mass spectrometry in the detection and quantification of phosphopeptides

Abstract: This one-to-one comparison of two interference-reducing ICP-MS instruments demonstrates that absolute quantification of individual LC-separated phosphopeptides is possible. However, based on the LOD values, SF-ICP-MS has a higher sensitivity in detecting phosphorus signals and thus is preferred in phosphopeptide analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…These features were already exploited for detection of phosphorus in small amounts of protein samples and for detection of metal complexes in rat liver . A direct comparison of sector-field ICP-MS and quadrupole ICP-MS with reaction cell showed that the interference removal with sector-field ICP-MS is more efficient for biological samples. , However, all of these previous studies suffered from the fact that increasing mass resolution causes loss of sensitivity - already the switch from low ( m / z = 300) to medium ( m / z = 4000) mass resolution causes an about 10× lowering of signal intensity. In all examples shown in the current study, medium resolution mode was used, which resolved all interferences on all elements shown here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These features were already exploited for detection of phosphorus in small amounts of protein samples and for detection of metal complexes in rat liver . A direct comparison of sector-field ICP-MS and quadrupole ICP-MS with reaction cell showed that the interference removal with sector-field ICP-MS is more efficient for biological samples. , However, all of these previous studies suffered from the fact that increasing mass resolution causes loss of sensitivity - already the switch from low ( m / z = 300) to medium ( m / z = 4000) mass resolution causes an about 10× lowering of signal intensity. In all examples shown in the current study, medium resolution mode was used, which resolved all interferences on all elements shown here.…”
Section: Resultsmentioning
confidence: 99%
“…The most significant single enhancement may be the development of a double focusing optics, leading to so-called sector-field ICP-MS. This has been shown to greatly enhance sensitivity, compared to conventional quadropole ICP-MS, while eliminating most matrix interferences. , Triple quadrupole ICP-MS improves the removal of matrix interferences compared to conventional single-quadrupole instruments as well, but a direct comparison to sector-field ICP-MS for biological samples was not yet published. Further sensitivity was gained in all ICP-MS types by replacing the standard spray chamber with a desolvating nebulizer (Apex Q, Elemental Scientific, Omaha, NE, USA).…”
mentioning
confidence: 99%
“…Se) [158][159][160][161] or non-metal (e.g. P) [162][163][164][165][166][167][168] and on elements added through derivatisation (e.g. I, Cu Eu, Lu) [169][170][171][172][173][174].…”
Section: Peptide Quantification By Determination Of Other Ele-mentioning
confidence: 99%
“…In this case, O 2 and O 2 /He have been adopted to convert the interfering species into PO + and SO + species. [45][46][47] In one study for P + detection, He was found to provide a better signal-to-noise ratio than using H 2 as the collision gas. 48 Mn is another example of a monoisotopic element which is impossible to detect among alternative isotopes; at the same time, it suffers interference from the Ar-, N-, and O-containing species.…”
Section: Collision/reaction Cell Gas System (Crc)mentioning
confidence: 99%
“…For example, sector-eld ICP-MS (SF-ICP-MS) operating at a resolution of 4000 can resolve the spectral interference for phosphorus determination. 46 However, one drawback of HR-ICP-MS is that, due to the requirements of high mass resolution analysis, the ion transmission efficiency is greatly diminished (e.g. 10-fold reduction).…”
Section: High Mass Resolution Icp-msmentioning
confidence: 99%